The courage to teach : exploring the inner landscape of a teacher's life - Palmer, Parker J. (Jossey-Bass, 2017)
"Exploring the inner landscape of a teacher's life is difficult to do alone or without guidance for reflecting on what THE COURAGE TO TEACH means to the reader. This guide is a welcome resource for those who wish to extend their exploration beyond just reading the book, individually or within a study group. Includes online video content featuring an interview with Parker Palmer discussing the crisis in education, the heart of a teacher, ways of knowing, the importance of relationship in teaching and learning, teacher renewal, and spirituality in education"--